The role of VGF and its derived peptides in the regulation of energy homeostasis - Lewis, Jo Edward (2015)
The VGF gene (non-acronymic) was first implicated in energy homeostasis by VGF-/- null mice, which were lean, hypermetabolic and hyperactive, suggesting an anabolic role for VGF (Hahm et al., 1999). Furthermore, VGF-/- mice were resistant to obesity induced by diet and genetic manipulation (Hahm et al., 2002). While VGF mRNA was reduced in response to short photoperiod, which is associated with reduced food intake and the utilisation of intra-abdominal fat stores in the Siberian hamster (Barrett et al., 2005; Ebling, 2014). However subsequent studies in Siberian hamsters and mice have suggested a catabolic role for the VGF derived peptide TLQP-21 (Bartolomucci et al., 2006; Jethwa et al., 2007). Thus the aim of this thesis was to further investigate the role of VGF in the regulation of energy homeostasis in the mouse and Siberian hamster. The studies presented in this thesis have shown that VGF derived peptide HHPD-41 can affect short term food intake in the Siberian hamsters, while overexpressing VGF mRNA in the hypothalamus of both Siberian hamsters and mice reduced bodyweight. However, this reduction in body weight was associated with an increase in both food intake and energy expenditure. These effects of VGF overexpression were attenuated in disrupted models of energy regulation. Finally these studies identified novel regulators of the VGF gene in vitro to postulate a possible mechanism for the seasonal regulation of appetite in the Siberian hamster. Collectively, the studies described in this thesis demonstrate a role for VGF in the regulation of energy homeostasis and contribute to increasing our understanding of how the brain regulates food intake.